Pembiayaan Syariah di Bank Perkreditan Rakyat Syariah pada Masa Pandemi Covid-19 - Muthoifin Muthoifin; Aisyah Nurhayatii; Amrin, Amrin,; Ahmad Imam Hambali (Prosiding University Research Colloquium, 2022)
Globally, the COVID-19 pandemic has affected changing in the decline in the worldeconomy, including the Islamic banking industry, but the performance of BPRS stillshows a positive direction. Therefore, this study is interested in discussing theimplementation of sharia compliance in murabahah contracts at BPRS Dana AmanahSurakarta murabahah which is one of the most widely applied types of contracts inIslamic banking financing activities and the impact of the pandemic on murabahahcontracts. The purpose of this study is to examine sharia compliance in theimplementation of murabahah contracts and the impact of the pandemic on murabahahcontracts at BPRS Dana Amanah Surakarta. This research is a field research with aninterpretive approach. Data analysis in this study uses content analysis which analyzesthe main sources of research in the form of interview data and contract documentsrelated to murabahah at BPRS Dana Amanah Surakarta. The conclusion is that thereare two kinds of murabahah financing: Sindication and non sindication. And there aaretwo kinds of murabaha contracts, namely the murabahah bil wa'ad lil syira contract andthe murabahah bi wakalah contract. In the murabahah bil wakalah contract, there aretwo schemes, the first is direct payment to the supplier and the second is paymentthrough the customer's account. Sharia compliance in the murabahah contract is inaccordance with sharia and the DSN-MUI fatwa, there is only a slight difference in theapplication of the second scheme of murabahah bil wakalah with the DSN-MUI fatwa.